Behavior of the Biological Control Agent Bacillus thuringiensis subsp. aizawai ABTS-1857 and Salmonella enterica on Spinach Plants and Cut Leaves - Zhao, Xingchen; Silva, Marcelo Belchior Rosendo da; Van der Linden, Inge; Franco, Bernadette D. G. M.; Uyttendaele, Mieke (Frontiers in Microbiology, 2021)
Fresh produce has been identified as an important vehicle for the transmission of foodborne pathogens. This study evaluated the behaviour of vegetative cells and spores of Bacillus thuringiensis , one of the main biological control agents (BCAs) used in the world, and Salmonella enterica on spinach plants (pre-harvest) and spinach cut leaves (post-harvest) at 12 oC, experimentally inoculated as single or co-cultures. The results evidenced that spray-inoculated commercial BCA containing Bacillus thuringiensis subsp. aizawai ABTS-1857 (BTa ABTS-1857) spores persisted well on spinach leaves in both pre- and post-harvest simulations. However, when BTa ABTS-1857 vegetative cells were spray-inoculated, more than 2 log reductions in the counts of B. thuringiensis were observed during 20 days pre- and 5 days post-harvest simulations, respectively. The counts of S. Montevideo on the spinach cut leaves during post-harvest storage at 12 °C for 5 days remained unchanged, whereas 1 log reduction was noted during pre-harvest. Moreover, during pre-harvest simulation, when co-inoculated with BTa ABTS-1857 vegetative cells or spores, additional 0.5 or 1.0 log reductions were detected on the counts of S. Montevideo in the spinach leaves on the 10th day. These results were obtained under laboratory conditions, and further findings in longitudinal studies from farm (in the agricultural field) to retail (end of shelf life) will contribute to understanding of the role of B. thuringiensis as a BCA on growth/survival of Salmonella spp. in fresh produce.